Anthelmintic efficacy of some medicinal plants to control mange in goat in Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
Parasitism is an important limiting factor that responsible for deteriorating the health and productivity of livestock. Goat rearing is hindered by various problems, among them parasitism is an important limiting factor in Bangladesh as the climatic condition of the country favors the development and survival of various parasites. Of the parasitic problems, ectoparasitic infestations are commonly seen in goats. Common ectoparasites of animals are ticks, lice and mites which cause considerable amount of blood loss, irritation and annoyance. Mange infested goats bite and rub the affected area so that the affected skin becomes abraded. Ectoparasitic infestations reduce the quality and market value of valuable skin. Besides, ectoparasites transmit various types of deadly pathogens of animals. The objectives of this study to find out the alternative measures of mange control especially with herbal products. In the experimental study of mange control, fifteen affected goats of both sexes, aged between 10 and 30 months which were divided into four groups randomly and 3 goats were considered in each group. The treatments were considered with control (A), Neem ointment (B), Ata ointment (C), Mehedi ointment (D).The control experiment was conducted during November’2012 to December’2012 in Rajshahi district of Bangladesh. A descriptive statistical analysis and ANOVA were used for the results of clinical parameters (hair coat, skin lesion bodyweight and adverse effects). The recovery of skin lesion was statistically significant (P0.10).The bodyweight was increased in all treatment groups and it was decreased in control group which was significant (P>0.10).In the herbal ointments, Neem(Azadirachtaindica) was more effective for control of mange in goats than Mehidi (Lawsoniainermis) and Ata (Annonareticulata). Further studies are required to clarify the efficacy of the ethno veterinary widely used in agro ecologies, animal species and livestock management system in Bangladesh.Res. Agric., Livest. Fish.6(3): 389-396, December 2019